Construction of substituted pyrazolo[4, 3‐c]quinolines via [5+1] cyclization of pyrazole‐arylamines with alcohols/amines in one pot. (13th December 2021) - Tang, Dong; Mu, Yangxiu; Iqbal, Zafar; He, Lili; Jiang, Rui; Hou, Jing; Yang, Zhixiang; Yang, Minghua
Abstract: An efficient protocol has been developed for the synthesis of pyrazolo[4, 3‐c]quinoline derivatives, by reacting (1 H ‐pyrazol‐5‐yl)anilines and readily available alcohols/amines. A wide range of substrates with diverse functional groups were smoothly converted to the corresponding products in moderate to good yields, under optimal reaction conditions. Furthermore, the strategy also proceeded well with thiol and amino acid to access pyrazolo[4, 3‐c]quinoline derivatives. Abstract :